Corporate strategy for PT Aqua Golden mississippi Jakarta-Indonesia - Soegito, Nita Nirmala Lestari (Animo Repository, 1998)
PT. AQUA GOLDEN MISSISSIPPI is the first and foremost bottled water producer in Indonesia. It was established in February 1973 and listed in the Indonesia Stock Exchange on March 1, 1990. The distribution and development of water supply in Indonesia is handled by the state-owned water company, Perusahaan Air Minum (PAM) the existing usable fresh water supply in the country have been severely strained by population explosion and industrial growth. The use of agricultural chemical and the disposal of toxic and hazardous substances have further compounded the problem. Public water treatment systems managed by PAM have become increasingly overtaxed leading to outbreaks harmful organisms. In many instance, water treatment systems work perfectly well at the source providing excellent water quality only to be later contaminated in the delivery pipeline leading to water of questionable quality at the tap, have become increasingly over-taxed leading to outbreaks of harmful organisms. The factors mentioned above contribute to the fast growth of the bottled water industry. Many mineral water companies have opened in Indonesia. Other factors are the changing of consumption behavior of consumers where they have turned to healthful living and are looking for natural beverages, products that are calorie-free and not laden with additives and bottled water perceived to be pure, natural and safer than water from the tap. The economic crisis that started in the second half of 1997 presents many challenges for Indonesias bottled water industry. Currency devaluation in the Asia Pacific Region resulted to extreme lack of liquidity and highly volatile exchange and interest rates. There is a decline in prices of shares listed in the Indonesian Stock Exchange thereby tightening available credit, stopping or postponing construction projects and there is a growing oversupply of real property. Producers are feeling pressure to raise prices due increase in production costs while growing unemployment and rising costs of living are cutting consumer purchasing power.